Application and functions of fat replacers in low-fat ice cream: A review. (April 2019) - Akbari, Mehdi; Eskandari, Mohammad Hadi; Davoudi, Zahra
Abstract: Ice cream as a complex multi-phase food consists of fat globules, air bubbles and ice crystals dispersed in a semi-frozen solution. Ice cream contains about 12% fat, which plays a significant role in ice cream structural and organoleptic properties. On the other hand, consumers are interested in consuming low-fat foods. Consequently, nowadays many fat replacers are utilized in low-fat ice cream that can mitigate textural and sensory defects caused by reducing fat content. Fat replacers are categorized into three groups based on their compositions: lipid, protein and carbohydrate-based. Most common fat replacers used in ice cream include inulin, maltodextrin, polydextrose, milk proteins, soy proteins, dietary fibers, and starches. In the current paper, these different types of fat replacers and their effects on the physicochemical and sensory properties of low-fat ice cream are discussed and compared. Highlights: No fat replacer is suitable for all applications in low-fat ice cream formulations. Suitable melting behavior in low-fat ice cream is not easily provided by using fat replacers. Conflicting results have been reported by recent researches regarding the inulin effect on ice cream melting properties.